Palms and People in the Amazon - Smith, Nigel (Geobotany Studies, Basics, Methods and Case Studies,, 2015)
This book explores the degree to which landscapes have been enriched with palms by human activities and the importance of palms for the lives of people in the region today and historically. Palms are a prominent feature of many landscapes in Amazonia, and they are important culturally, economically, and for a variety of ecological roles they play. Humans have been reorganizing the biological furniture in the region since the first hunters and gatherers arrived over 20,000 years ago.